2016
DOI: 10.4103/2230-8229.181011
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity and overweight and obesity in a population of children at high and low altitudes in Southwestern Saudi Arabia

Abstract: Objective:To assess the relationship between overweight and obesity and physical activity in Saudi children born and permanently domiciled at high and low altitudes in Southwestern Saudi Arabia.Subjects and Methods:A cross-sectional study of 145 healthy Saudi children aged 10–15 years who were born and lived permanently at high altitude (3000–3100 m) and 154 healthy Saudi children of comparable age who were born and lived permanently at a relatively low altitude (500 m) was conducted. For each subject selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…The results showed that the respondents didmoderate physical activity. Similar to research conducted by Ahmed et al date(2016)that physical activity undertaken is a moderate physical activity [21]. In this study, the majority of respondents did physical activities organized by the school, namely, during sports lessons with 2-3 times a week sports activity such as aerobics, dancing, or playing which were very effective after returning home at night on weekends.…”
Section: Discussionsupporting
confidence: 80%
“…The results showed that the respondents didmoderate physical activity. Similar to research conducted by Ahmed et al date(2016)that physical activity undertaken is a moderate physical activity [21]. In this study, the majority of respondents did physical activities organized by the school, namely, during sports lessons with 2-3 times a week sports activity such as aerobics, dancing, or playing which were very effective after returning home at night on weekends.…”
Section: Discussionsupporting
confidence: 80%
“…Table 2 illustrates the reasons for being active and the correlates of (or barriers to) PA among Saudis. [14,16,18,19,23,26,28-32,38,40,41,43,45,49,50,53,65] The present review shows that the most important reasons for engaging in PA among adolescents and adults are health, losing or maintaining weight, recreation, and socializing. The most important barriers to PA among adolescents are the lack of time in both males and females, followed by no appropriate place, especially in females and lack of facility and resources.…”
Section: Resultsmentioning
confidence: 75%
“…This finding applies to studies involving children and adolescents,[14,19-21,52,64] as well as to those studies reporting PA data for adults. [28,30,37,38,41,45,47,48,65,66,67] In one study involving females from Riyadh between 19 and 44 years, the mean daily step counts were considerably low (5114 steps). [67] Such low mean daily steps placed them in the low active category, according to some proposed pedometer-determined PA standards.…”
Section: Resultsmentioning
confidence: 99%
“…In Oman (2000) the prevalence of overweight and obesity was 46.2% for males and 49.5% for females with a crude prevalence of 47.9% for the whole sample. (24) The current study found that most of studied employees (86.2%) did not practice sports at all and the difference between males and females was statistically insignificant. However, in Egypt, Khalid (1995) revealed that women were less active compared to men in certain areas.…”
Section: Discussionmentioning
confidence: 46%
“…(24) The current study found that most of studied employees (86.2%) did not practice sports at all and the difference between males and females was statistically insignificant. However, in Egypt, Khalid (1995) revealed that women were less active compared to men in certain areas. Physical and cultural barriers to physical activity have been reported among women in Egypt.…”
Section: Discussionmentioning
confidence: 46%